TÜRK SPOR EĞİTİMİNDE SPOR TESİSLERİNİN YETERLİLİK DÜZEYLERİNİN BELİRLENMESİ - NACAR, EYYÜP (Fırat Üniveristesi, 2011)
Araştırmanın amacı, Türkiye'de yükseköğretim kurumlarında spor eğitimi veren birimlerde yer alan spor tesislerinin nitelik ve nicelik açısından mevcut durumu tespit edilerek, spor tesislerinin beden eğitimi ve spor eğitimi veren kurumların, müfredat programları doğrultusunda kullanım alanları ile yeterlilik ve kapasite düzeylerinin araştırılmasıdır.Araştırmanın evrenini, Türkiye'de spor eğitimi veren kurumlar oluşturmakta olup, örneklemini ise, yüksek öğretim kurumlarında spor eğitimi veren bölümler oluşturmaktadır.Araştırma üç bölümde değerlendirilmiştir. Birinci bölümde, Türkiye'de spor eğitimi veren üniversiteler ve spor tesislerine ait bilgilere yer verilmiştir. İkinci bölümde araştırmaya katılan, üniversitelerde, spor eğitimi veren bölümlerde, görev yapan yöneticilere yönelik, ?Spor Tesislerinin Yeterlik Düzeylerinin Belirlenmesi?ni içeren anket uygulanmıştır. Üçüncü bölümünde ise; ilgili anketin, demografik bilgilerde yer alan yöneticilere, çalıştıkları üniversitelerinin bulundukları coğrafi bölge ve yönetsel görev değişkenlerine yönelik, istatistiki değerlendirmelere yer verilmiştir.Araştırma verilerinin elde edilmesi sonucunda elde edilen veriler istatistik SPSS 17.0 paket programından yararlanılarak, yüzde, frekans , aritmetik ortalama ve ?² (chi-square) testi uygulanmıştır. Elde edilen sonuçların anlamlı bulguları tablo ve grafiklerle gösterilmiş, yapılan analizlerde anlamlılık düzeyi p<0.05 olarak kabul edilmiştir.Sonuç olarak Türkiye'de yüksek öğretim kurumlarında spor eğitimi veren birimlerdeki spor tesisleri sayısal açıdan yetersiz olduğu gözlemlenmiştir.Spor tesislerinin yeterlilik düzeylerinin belirlenmesine yönelik uygulanan, anket sonuçlarına göre katılımcıların, ?spor tesisleri nitelik ve nicelik bakımından yeterli olmadığı?, ?spor tesislerinin yetersizliğinin, siyasi iktidarların spor tesislerine gereken önemi vermediğinden? kaynaklandığı görüşlerine yer verdikleri, eğitim-öğretim kalitesi bakımından ?her bölümün kendine ait spor tesislerinin olması? ve ?spor tesislerin eksikliğinin öğretim kalitesini düşürdüğünün? görüşleri tespit edilmiştir.

The purpose of the survey is to make an inquiry of the usage areas and their efficiency and the capacity levels in line with the curriculum of the sports facilities of the institutions that give physical training and sports training by determining the present position in respect of the quality and quantity of the sports facilities at the units that give sports training at the higher education institutions in Turkey.The nature of the survey is consisted of the departments of the institutions that give sports training in Turkey and the sampling is consisted of the departments that give sports training at the higher educational institutions.The survey was assessed in three parts. In the first part, information was given about the universities and the sports facilities in Turkey that give sports training. In the second part a questionnaire, consisted of ?Specifying the Level of Efficiency of the Sports Facilities ? has been applied, which was directed towards the directors that perform a duty at the universities and the departments that give sports training that participated to the survey. And in the third part, the statistical assessments were included in the relevant questionnaire, directed towards the directors that take part in the demographic information and the variables of the geographical region where the universities they work with are located and of the executive officesPercent, frequency , arithmetical average and ?² (chi-square) tests have been applied to the data, obtained as the result of the reached survey data, by making use of the statistical SPSS 17.0 package programme. The significant findings of the obtained results have been shown on a table and through graphics, and the significance level in the made analyses was accepted as (p<0.05).As a conclusion, it was observed that the sports facilities at the units giving sports training at the higher educational institutions in Turkey were insufficient with respect to their numbers.According to the results of the questionnaire applied directed towards determining the efficiency level of the sports facilities, the opinions of the participants that ?the sports facilities with respect to quality and quantity are not efficient?, that ?the reason of the inefficiency of the sports facilities is due to the political powers who don?t attach the necessary importance to them? were considered, and with respect to the training quality, the opinions that ?every single department should have its own sports facilities? and ?the lack of sports facilities decreases the educational quality? were expressed.
The topic of the survey is ?Specifying the level of efficiency of the sports facilities in the Turkish sports training?
Keywords: Spor